PENGARUH LEVERAGE DAN CASH HOLDING TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Lia Nofita; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to partially and simultaneously examine the effect of leverage and cash holding on firm value. Where the independent variables in this study are leverage and cash holding and the dependent variable is firm value.     This study uses secondary data in the form of company financial statements and annual reports of property and real estate companies that are listed on the Indonesia Stock Exchange in 2012-2016. Sampling using a purposive sampling technique, which is used by 16 companies. Data analysis using simple linear regression analysis, multiple linear regression analysis, T test, F test and coefficient of determination test using SPSS 23.     The results of the analysis show that partial leverage (t test) affects the value of property and real estate companies listed on the Indonesia Stock Exchange, cash holding variables partially (t test) affect the value of property and real estate companies listed on the Exchange Indonesian effect. Simultaneous test results (test f) show the influence of leverage and cash holding variables on the value of the company in property and real estate companies listed on the Indonesia Stock Exchange.   Keywords: Leverage, Cash Holding, and Company Value